The Effect of Financing on Deposit Ratio, Return on Assets, and Third-Party Funds on Musyarakah Financing in Sharia Banks - Vena Vebriyana Puji Lestari; Triana Rahayu Sukma; Agung Yulianto; Itah Miftahul Ulum (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aimed to determine how Islamic Commercial Banks' Musyarakah Financing was affected by Return on Asset (ROA), Financing to Deposit Ratio (FDR), and Third Party Funds (DPK) between 2021 and 2024. The secondary data utilized originates from the Islamic Commercial Banks' published quarterly financial report data. With a sample size of nine banks, the study's population included 144 Islamic Commercial Bank financial reports and 14 Islamic Commercial Banks. Purposive sampling was employed in the sampling procedure. The Descriptive Statistical Test, Chow Test, Hausman Test, Classical Assumption Test, Heteroscedasticity Test, T Test, and Determination Coefficient Test (R²) are among the statistical tests used in panel data regression utilizing Eviews version 12 software. The findings indicated that return on assets (ROA) had an impact on Musyarakah financing, third party funds (DPK) had no effect, and the financing to deposit ratio (FDR) had a favorable impact.